Social rights, citizenship, and democratic management: contributions to the critical debate - Guimarães, Jairo de Carvalho (Argumentum, 2022)
The study describes relationships involving democratic management, social rights, and citizenship, against the backdrop of the Democratic Rule of Law. An analysis is developed regarding the implications for social arrangements, notably those with the highest levels of fragility, regarding the reduction, suppression, or cessation of social rights in apparently democratic territories. The theoretical thrust is substantiated by considerations regarding the factors surrounding democratic order and aspects that supposedly guarantee a democracy legitimized by the right to universal suffrage. It is inferred that democratic management presupposes the adoption of public policies aimed at the common good, aimed at meeting society’s demands through systematic and permanent actions to combat poverty and mitigate social inequalities.